A Phase II randomised controlled trial assessing the feasibility, acceptability and potential effectiveness of Dignity Therapy for older people in care homes: Study protocol - Hall, Sue (BioMed Central, 2009)
BACKGROUND: Although most older people living in nursing homes die there, there is a dearth of robust evaluations of interventions to improve their end-of-life care. Residents usually have multiple health problems making them heavily reliant on staff for their care, which can erode their sense of dignity. Dignity Therapy has been developed to help promote dignity and reduce distress. It comprises a recorded interview, which is transcribed, edited then returned to the patient, who can bequeath it to people of their choosing. Piloting has suggested that Dignity Therapy is beneficial to people dying of cancer and their families. The aims of this study are to assess the feasibility, acceptability and potential effectiveness of Dignity Therapy to reduce psychological and spiritual distress in older people reaching the end of life in care homes, and to pilot the methods for a Phase III RCT. METHODS/DESIGN: A randomised controlled open-label trial. Sixty-four residents of care homes for older people are randomly allocated to one of two groups: (i) Intervention (Dignity Therapy offered in addition to any standard care), and (ii) Control group (standard care). Recipients of the "generativity" documents are asked their views on taking part in the study and the therapy. Both quantitative and qualitative outcomes are assessed in face-to-face interviews at baseline and at approximately one and eight weeks after the intervention (equivalent in the control group). The primary outcome is residents' sense of dignity (potential effectiveness) assessed by the Patient Dignity Inventory. Secondary outcomes for residents include depression, hopefulness and quality of life. In view of the relatively small sample size, quantitative analysis is mainly descriptive. The qualitative analysis uses the Framework method. DISCUSSION: Dignity Therapy is brief, can be done at the bedside and could help both patients and their families. This detailed exploratory research shows if it is feasible to offer Dignity Therapy to residents of care homes, whether it is acceptable to them, their families and care home staff, if it is likely to be effective, and determine whether a Phase III RCT is desirable. TRIAL REGISTRATION: Current Controlled Clinical Trials: ISRCTN37589515